Jane's all the world's aircraft, 1994-1995 - Lambert, Mark; Munson, Kenneth (Jane's Information Group, 1994)
Provides details of aircraft and aero-engines from 50 countries. For each entry, details are given of the development programme, operational uses, current versions and customers. Also detailed are aerodynamic features, propulsion, dimensions, weights and loadings. Also available on CD-ROM and EIS.